2014
DOI: 10.1016/j.foodcont.2013.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Production, stability, gene sequencing and in situ anti-Listeria activity of mundticin KS expressed by three Enterococcus mundtii strains

Abstract: a b s t r a c tThree enterococci (WFE3, WFE20 and WFE31) selected as presumptive bacteriocin producers were found to be active against Listeria monocytogenes. In this study, due to their potential industrial/food applications, the three bacterial isolates were extensively characterized. Identification was performed by means of a combined 16S rRNA gene sequencing and multiplex PCR approach, and was confirmed with the sequencing of a partial region of a protein-encoding gene, namely pheS. The three isolates belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 55 publications
4
8
0
Order By: Relevance
“…Similar results have been reported by other researchers (Settanni et al, 2014;Vera Pingitore, Todorov, Sesma, & Gombossy de Melo Franco, 2012). Meanwhile, all three examined strains showed high inhibition activities for Gram-negative pathogens, such as K. pneumoniae and S. flexneri.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results have been reported by other researchers (Settanni et al, 2014;Vera Pingitore, Todorov, Sesma, & Gombossy de Melo Franco, 2012). Meanwhile, all three examined strains showed high inhibition activities for Gram-negative pathogens, such as K. pneumoniae and S. flexneri.…”
Section: Discussionsupporting
confidence: 90%
“…In that work, E. faecalis persisted longer than other species during ripening. This species, together with E. faecium, E. durans, Enterococcus mundtii and E. casseliflavus, is commonly found in many raw materials and foods (Corsetti et al, 2007;Franciosi et al, 2009;Settanni et al, 2014).…”
Section: Species Distributionmentioning
confidence: 99%
“…On the contrary, none of the enterocin A, B, P and L50A/B structural genes could be amplified suggesting that the corresponding gene clusters were not present in E. mundtii. In particular, only a few studies reported the inhibitory action of bacteriocins produced by E. mundtii (Pingitore, Todorov, Sesma, & Franco, 2012;Settanni et al, 2014). It must be highlight that mundticin KS produced by E. mundtii Tw56 was active against Gram negative bacteria, an unusual characteristic for bacteriocin produced by LAB.…”
Section: Pcr Screening For Bacteriocins Structural Genesmentioning
confidence: 99%